2008
DOI: 10.1128/jvi.00846-08
|View full text |Cite
|
Sign up to set email alerts
|

The Broadly Neutralizing Anti-Human Immunodeficiency Virus Type 1 4E10 Monoclonal Antibody Is Better Adapted to Membrane-Bound Epitope Recognition and Blocking than 2F5

Abstract: The broadly neutralizing 2F5 and 4E10 monoclonal antibodies (MAbs) recognize epitopes within the membrane-proximal external region (MPER) that connects the human immunodeficiency virus type 1 (HIV-1) envelope gp41 ectodomain with the transmembrane anchor. By adopting different conformations that stably insert into the virion external membrane interface, such as helical structures, a conserved aromatic-rich sequence within the MPER is thought to participate in HIV-1-cell fusion. Recent experimental evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
68
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 90 publications
10
68
2
Order By: Relevance
“…Enhanced binding of mAb 2F5 and mAb 4E10 to their epitopes was observed in a lipid environment compared with free MPER peptides [23][24][25][26]. These findings raise the question, whether membranes or …”
Section: Introductionmentioning
confidence: 66%
“…Enhanced binding of mAb 2F5 and mAb 4E10 to their epitopes was observed in a lipid environment compared with free MPER peptides [23][24][25][26]. These findings raise the question, whether membranes or …”
Section: Introductionmentioning
confidence: 66%
“…2F5 and 4E10 may exploit the naturally occurring motion and flexibility at the MPER N terminus and hinge to extract buried hydrophobic residues to achieve tight binding. Taken together, these BNAbs may interfere with viral fusion by inhibiting membrane disruption at an early stage and/or by blocking interaction between the MPER and the other region(s) of gp41 at a late stage (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial findings by Grunder et al and Ofek et al (12,22), a number of publications have also shown that 2F5, 4E10, and Z13e1 improve binding to Env and epitope peptides in a lipid environment (21,23,24). In addition, it has become increasingly clear that 4E10 binds to lipids in the absence of the MPER (21,(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In addition, it has become increasingly clear that 4E10 binds to lipids in the absence of the MPER (21,(23)(24)(25)(26)(27)(28)(29). These studies have generated models of 4E10 epitope recognition (21,23), but they have not yet fully addressed which antibody region(s) bind lipid and, of particular importance for vaccine design, whether lipid interaction is an essential component of MPER-mediated neutralization.…”
mentioning
confidence: 99%